Perioperative antibiotic prophylaxis - Mosquera Fernández, Abián; Souto Rey, Victoriano; Carrodeguas, María Vale; García Castro, Ricardo (Revista Internacional de Ciencias Podológicas, 2013)
The main goal of antibiotic prophylaxis is to decrease the grade of bacterial colonization in the surgical wound. However this only represents one of many preventive measures that contribute to avoid a postsurgical infection. Because at present there is no recognized protocol for the use of antimicrobials within Podiatric Surgery the authors have reviewed the current literature in order to encourage an adequate praxis and so to avoid adverse effects derived from an inappropriate use. The authors believe that the performance of surgery must determine a minimum knowledge of antibiotic prophylaxis, its indications and contraindications for patient’s benefit.